2018
DOI: 10.3151/jact.16.110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silicone Oil on Durability of Portland Blast Furnace Slag Cement Mortar

Abstract: In this study, the development of carbonation resistance in blast furnace slag (BFS) mortar when using silicone oil (SO) is investigated. Moreover, the influence of SO on drying shrinkage and frost resistance are investigated. The results indicate that SO tends to improve the carbonation resistance of BFS blended mortar and reduces drying shrinkage; however, it decreases frost resistance. The water repellency of SO has a positive effect on carbonation and drying shrinkage. Furthermore, there is a possibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…When pores whose diameter is different are adjacent, moisture inside the pores is moved to a smaller-diameter pore due to capillarity. However, if silicone oil, which is water repellent, is added, the pore wall will have the water repellent property, resulting in difficulties in moisture travel to a smaller diameter pore, but easy moisture travel to a larger diameter pore [13,24]. Accordingly, as the capillary tension inside the pore was smaller, shrinkage was likely to be reduced significantly.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When pores whose diameter is different are adjacent, moisture inside the pores is moved to a smaller-diameter pore due to capillarity. However, if silicone oil, which is water repellent, is added, the pore wall will have the water repellent property, resulting in difficulties in moisture travel to a smaller diameter pore, but easy moisture travel to a larger diameter pore [13,24]. Accordingly, as the capillary tension inside the pore was smaller, shrinkage was likely to be reduced significantly.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…SO0, to which silicone oil was not added, maintained 100% of the relative dynamic elastic modulus even at the time when 300 cycles were passed whereas the relative dynamic elastic modulus of silicone oil-added SO3 or SO5 specimen tended to decrease somewhat. The previous studies [13,24] explained that the water pressure reducing mechanism due to the entrained air was not working, which was inherently expected, as the movement of non-frozen water was reduced due to the silicone oil when the moisture inside the capillary pore was frozen because silicone oil is present as a form of oil droplet inside the pore if the silicone oil is added. The same tendency could also be verified in ECO-FRPCM.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honda et al [12] reported that the addition of paraffin as a hydrophobic compound to mortar would improve its resistance to frost damage. Kishimoto et al [13,14] suggested that the addition of an appropriate amount of silicone oil also improved frost resistance. The results showed that the amount of air bubbles increased with the addition of the hydrophobic compound (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many research attempts were made to enhance the durability of concrete by either altering its composition or by using different types of additives and admixtures 4–9 . Accordingly, hydrophobic materials were used as surface impregnates to control the deterioration of concrete caused by the ingress of water and aggressive chemicals 3,10–17 . Silane and siloxane were the most commonly employed hydrophobic materials in this respect owing to their strong tolerance to various environmental effects and chemical attacks 18–24 .…”
Section: Introductionmentioning
confidence: 99%